Meteorological conditions and particulate material PM10 and PM2.5 in the construction of the hospital Hipólito Unánue, Tacna 2019 - Motocanche Ayala, Diego (2020)
The study was based on the influence of meteorological conditions on the dispersion of PM10 and PM2.5 atmospheric pollutants during the construction of Hipólito Unánue Hospital in Tacna from June to September 2018. The sampling methodology and analysis was based on the DIGESA air quality monitoring and data management protocol (2005). The 2 monitoring stations EMHU-01 and EMHU-02 registered in the month of June for PM2.5 values of 69.53 and 63.04 ug/m3 and in the month of September in the station EMHU-01 the value of 64.40 ug/m3 which exceeded the environmental quality standard for air. These values were directly related to the high temperature values of 18 and 19.6 °C and the wind speed of 2.5 m/s and an inverse relationship with the relative humidity of 76.3 and 75%. In addition, the analysis of the variance determined that there is no significant difference between the data obtained and both variables were corroborated with the Pearson statistical test (r) 0.705, the correlation coefficient p-value (sig = 0.016) and with a level of significance less than 0.05